Mechanistic insights on the electronic properties and electronic/atomic structure aspects in orthorhombic SrVO3 thin films: XANES–EXAFS study. Issue 9 (15th February 2017) - Sharma, Aditya; Varshney, Mayora; Cheol Lim, Weon; Shin, Hyun-Joon; Pal Singh, Jitendra; Ok Won, Sung; Hwa Chae, Keun
Abstract : Distortion in the V–O6 octahedra is observed in SrVO3 thin films and leads to larder separation between bonding and anti-bonding d‖ orbitals. Abstract : Correlations among the B–O6 octahedra distortions, existing polymorphous phases, band structures and electronic conductivities of ABO3 perovskites are matters for debate and require a deep understanding of their local atomic/electronic structures and diverse assets. In this study, to illustrate the distortion in V–O6 octahedra and its implication on the band structure and electronic properties, spectroscopic investigations on the RF-sputtering grown insulating SrVO3 thin films were employed using X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS). V K-edge and V L3, 2 -edge XANES, along with atomic multiplet calculations, have confirmed the 4+ oxidation state of V ions in the pristine and annealed SrVO3 thin films. Lower t2g /eg peak intensity ratio and smaller energy separation between t2g and eg peaks in the O K-edge XANES spectra, compared to the VO2 reference sample, have confirmed a larger V–O6 distortion in the orthorhombic SrVO3 thin films. Moreover, from the EXAFS data analysis, the local orthorhombic structure has been identified in the pristine and annealed SrVO3 thin films, compelling significant distortion in the V–O6 octahedra. Dimerization in the vanadium chains and V–V twisting, caused by V–O6 octahedra distortion, manifests a miscellaneous ligand field interaction between O 2p and V 3d orbitals and facilitates (i) a larger separation between the bonding and antibonding d‖ orbitals and (ii) an upward shift of the π* band in the band structure, leading to larger band gaps in the insulating SrVO3 thin films. Our spectroscopy results may open up new avenues for the mechanism of insulating/conducting character in other complicated perovskite materials using XANES–EXAFS.